GRID-Infrastructure simulation - Shelestov, A.Ju.; Kussul, N.N.; Skakun, S.V. (Інститут програмних систем НАН України, 2006)
In a paper simulation modelling of Grid infrastructure is carried out in order to investigate and analyze its productivity. For this purpose, GridSim modelling package is used. An approach based on the operational analysis is applied for the performance analysis of the Grid system. Such approach enables qualitative and quantitative estimation of the Grid system performance.